2021
DOI: 10.3389/fpls.2021.627403
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Key Points of Hydraulic Vulnerability Curves From Drought-Rewatering Experiment Using Differential Method

Abstract: Precise and accurate estimation of key hydraulic points of plants is conducive to mastering the hydraulic status of plants under drought stress. This is crucial to grasping the hydraulic status before the dieback period to predict and prevent forest mortality. We tested three key points and compared the experimental results to the calculated results by applying two methods. Saplings (n = 180) of Robinia pseudoacacia L. were separated into nine treatments according to the duration of the drought and rewatering.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Plant functional traits are important for exploring the relationship between plants and the environment, which provide a basis for predicting the response of ecosystems in the context of global change ( Wright et al, 2010 ; Li et al, 2015 ; Liu et al, 2021b ). Previous studies have suggested that plant functional traits are key to elucidating the mechanisms that drive the responses of plant communities and ecosystems to resource addition ( McGill et al, 2006 ; Suding and Goldstein, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plant functional traits are important for exploring the relationship between plants and the environment, which provide a basis for predicting the response of ecosystems in the context of global change ( Wright et al, 2010 ; Li et al, 2015 ; Liu et al, 2021b ). Previous studies have suggested that plant functional traits are key to elucidating the mechanisms that drive the responses of plant communities and ecosystems to resource addition ( McGill et al, 2006 ; Suding and Goldstein, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gas-exchange characteristics were measured between 9:00 and 11:00 on sunny days. During the measurement, temperature, relative humidity, and CO 2 concentration inside the chamber were controlled at 28°C, 50%, and 400 ppm, respectively ( Wang et al, 2020 ; Liu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…where L is the length of the segment (m), Q m is the mass of the water per unit of time through a segment (kg s –1 ), S is the average cross-sectional area for both ends of the stem (m 2 ), and p is the intensity of the water pressure across the segment (MPa) ( Liu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Hydraulic conductivity (K h , mL mm h −1 Pa −1 ) was calculated as K h = Jv/( P/ L), where Jv is the flow rate through the segment (mL h −1 ) and P/ L is the pressure gradient across the segment (Pa mm −1 ). Stem-specific hydraulic conductivity (K s , mL mm −1 h −1 Pa −1 ) was calculated as the ratio of K h to stem cross sectional area (mm 2 ) according to Liu et al (2015Liu et al ( , 2021.…”
Section: Stem Water Potential and Hydraulic Conductivitymentioning
confidence: 99%